2022
DOI: 10.1007/s41252-022-00239-9
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Dog-Assisted Therapy in Children with Behavioural and Developmental Disorders

Abstract: Objectives Animal-assisted therapy with dogs is regularly used in children with behavioural and developmental disorders. Aims of this systematic review were threefold: to analyse the methodological quality of studies on dog-assisted therapy (DAT) for children with behavioural and developmental disorders, to determine to which extent the studies on DAT adhere to the quality criteria developed by the International Association of Human Animal Interaction Organisation (IAHAIO) and to describe the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Database searches are ideal for sourcing literature in its infancy as they avoid missing cutting-edge articles published in specialty and niche journals. Thus, we began with a Advocacy (Gaarder, 2008;Haris, 2022) Shelter work (Frommer & Arluke, 1999; Hoy-Gerlach, Delgado, Sloane, & Arkow, 2019) Veterinary medicine (Black et al, 2011 Therapy (Hüsgen et al, 2022;Rostami Haji Abadi, Hase, Dell, Johnston, & Kontulainen, 2022) Law enforcement (Horváth, Dóka, & Miklósi, 2008;Sandrin et al, 2022) Service animals (Dell & Poole, 2015;Sedova, 2022 A manual review of all retrieved abstracts revealed high overlap and confirmed the comprehensiveness of our approach.…”
Section: Central Reviewmentioning
confidence: 69%
See 1 more Smart Citation
“…Database searches are ideal for sourcing literature in its infancy as they avoid missing cutting-edge articles published in specialty and niche journals. Thus, we began with a Advocacy (Gaarder, 2008;Haris, 2022) Shelter work (Frommer & Arluke, 1999; Hoy-Gerlach, Delgado, Sloane, & Arkow, 2019) Veterinary medicine (Black et al, 2011 Therapy (Hüsgen et al, 2022;Rostami Haji Abadi, Hase, Dell, Johnston, & Kontulainen, 2022) Law enforcement (Horváth, Dóka, & Miklósi, 2008;Sandrin et al, 2022) Service animals (Dell & Poole, 2015;Sedova, 2022 A manual review of all retrieved abstracts revealed high overlap and confirmed the comprehensiveness of our approach.…”
Section: Central Reviewmentioning
confidence: 69%
“…The second form of employee-animal interaction is the coworker relationship, wherein animals work with humans. This may entail either collaboration on the same task, such as conducting arrests in law enforcement (Hart, Zasloff, Bryson, & Christensen, 2000; Schuurman, 2021), or supporting patients in therapy (Cavalli, Carballo, Dzik, & Bentosela, 2019; Hüsgen, Peters-Scheffer, & Didden, 2022; Prothmann, Bienert, & Ettrich, 2006). Alternatively, animals support and supplement human work via their unique skills and capabilities.…”
Section: A Typology Of Employee-animal Interactionsmentioning
confidence: 99%
“…Unfortunately, this school was the only one, among other private and public schools that replied positively to the researchers' proposal to participate in this research. Therefore, any result generilisation should be done with serious consideration of the above limitations, since the size and the distribution of the sample is neither large nor necessarily representative (Grové et al, 2021;Hüsgen et al, 2022;Mitchell, 2019;Wintermantel & Grove, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…U istraživanjima povezanima sa psima pomagačima, terapijskim psima odnosno terapijom sa životinjama (AAT) najčešće su primjenjivani anketni upitnici ili intervjui s korisnicima i njihovim skrbnicima, zbog čega je ovo bila prilika da se istraživanje provede kroz primjenu opservacijskih upitnika koji sagledavaju samostalnost i napredak djeteta unutar terapijskih susreta i aktivnosti te kategorija MKF-a. 19 Iako u ovom istraživanju rezultati ukazuju na značajno manju podršku koja je djetetu potrebna u aktivnostima i regulaciji ponašanja nakon ASI-ja ® i AAT-a uz terapijskog psa, potrebno je ispitati utjecaj ovog terapijskog pristupa na funkcioniranje i samostalnosti djece u svakodnevnim životnim aktivnostima i okupacijama te senzoričkom funkcioniranju u svakodnevici. Također teško je odrediti koliki je bio utjecaj terapijskog psa ili ASI-ja ® te u kojem omjeru, a koji je dio rezultata posljedica biopsihosocijalnog razvoja djeteta.…”
Section: Rezultatiunclassified